2018
DOI: 10.1029/2018ms001305
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Evolution of Mesoscale Convective Systems: Sensitivity to Cloud Microphysics in Convection‐Permitting Simulations Over the United States

Abstract: Regional climate simulations over the continental United States were conducted for the 2011 warm season using the Weather Research and Forecasting model at convection‐permitting resolution (4 km) with two commonly used microphysics parameterizations (Thompson and Morrison). Sensitivities of the simulated mesoscale convective system (MCS) properties and feedbacks to large‐scale environments are systematically examined against high‐resolution geostationary satellite and 3‐D mosaic radar observations. MCS precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
226
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(251 citation statements)
references
References 70 publications
3
226
0
1
Order By: Relevance
“…Therefore, the suppression of shallow warm clouds is still evident to some extent. The aerosol‐induced larger stratiform/anvil region could affect the subsequent development of the convective system, as Feng et al () found more stratiform rainfall favor longer‐lived MCSs through stronger dynamical feedbacks.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the suppression of shallow warm clouds is still evident to some extent. The aerosol‐induced larger stratiform/anvil region could affect the subsequent development of the convective system, as Feng et al () found more stratiform rainfall favor longer‐lived MCSs through stronger dynamical feedbacks.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We only focus on CCN effects on the primary MCS. The feedback of the stratiform/anvil properties changed by aerosols to the development of subsequent convective systems, as discussed in Feng et al (2018), would be a good topic for future studies.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…Following Byers and Braham (1949) and Houze (1982), the life cycle of an MCS can be described in terms of three stages: developing, mature, and dissipating. The methods developed previously use different criteria to identify the life stages of cloud systems and track them using temporally continuous geosynchronous satellite and/or ground-based radar data (Feng et al, 2012;Feng et al, 2018;Futyan & Del Genio, 2007;Machado et al, 1998;Mathon & Laurent, 2001;Williams & Houze, 1987). Most of these criteria are based on MCS size, duration, and depth thresholds.…”
Section: Identifying the Stages Of Meiyu Precipitation Systemsmentioning
confidence: 99%
“…However, this leads to an increased production of snow, and in our model framework the anvil cloud cannot be sustained as long as for the M2005 microphysics. Feng et al (2018) compared the Thompson and M2005 schemes in high-resolution simulations of warm season convection over North America. They found that both schemes produced reasonable agreement with observations but that Thompson did a better job of simulating upper level clouds and matching the observed amount of stratiform precipitation.…”
Section: 1029/2018ms001484mentioning
confidence: 99%